Pendampingan Pemberantasan Buta Tulis Al-Quran Di Desa Bulangan Haji, Pegantenan Pamekasan - Mukit, Abdul; Mabrurrosi, Mabrurrosi; Arifin, Zainal; Baidowi, Baidowi; Ghoffari, Moh. Isbat Alfan; Tamam, Badrut (Al-Ridha: Jurnal Pengabdian kepada Masyarakat, 2024)
This study aims to explore and evaluate the assistance program for eradicating Quranic illiteracy in Bulangan Haji Village, Pegantenan, Pamekasan. The program was initiated in response to the high level of Quranic illiteracy among the village community. The methods used in this study include observation, interviews, and document analysis. Participants in this program come from various demographics, including children, teenagers, and adults. The research findings indicate that this assistance program successfully improved the participants' ability to read and write the Quran. Additionally, the program significantly enhanced religious awareness and learning enthusiasm within the community. Key factors contributing to the program's success include interactive teaching methods, community support, and the availability of adequate teaching materials. These findings highlight the importance of implementing similar programs in other areas with similar characteristics to broadly reduce Quranic illiteracy.